Portraying Peaceful Coexistence and Mutual Tolerance Between Santri and Chinese Community in Lasem - Sobirin, Mohamad (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
Coexistence and tolerance among the elite religious leaders in many cases seem not being considered as a problem, but at the grassroots level, the conflict often happened as an ironic phenomenon. This paper reveals and elaborates the socio-religious relations that existed between Santri and Chinese communities in Lasem—a small town located in the northern coastal part of the east end of the Central Java Province. The history recorded Lasem as one of the most important cities in Indonesia that bridged trading with China as early as the 14th century. It explains why Tionghoa villages (pecinan), as well as plenty of Konghucu’s religious worshipping sites (klenteng), could be found in the town and also legacy sites as a place of religious worshipping of Konghucu. On the other hand, Muslims with a strong religious level largely grew in this town. With the qualitative approach, this research found that there are some factors contributing to build six models of coexistence, tolerance, and respect for the socio-religious diversities among the societies as the attitudes toward plural societies which brought into socio-harmony of Lasem. The analyzed data obtained through observation and interviews with various parties which is the object of this research, such as Islamic masters (kyai) and students (santri) at Islamic boarding school (pesantren) in Lasem, community and religious leaders of Chinese-Confucianism, and also documents that describe the historicity of Muslims and Chinese in Lasem.Koeksistensi dan toleransi diantara kalangan elit pemuka agama dalam banyak kasus tampak tidak pernah ada permasalahan, namun pada kalangan grassroot tidak jarang konflik hadir sebagai fenomena yang ironis. Paper ini menampilkan hubungan sosial-keagamaan yang terjalin di antara komunitas santri dengan etnik Tionghoa beragama Konghucu di Lasem—kota kecil terletak di pantura bagian ujung timur provinsi Jawa Tengah. Sejarah mencatat bahwa Lasem adalah salah satu kota terpenting dalam peta pelayaran dan perdagangan China pada abad ke-16. Itulah mengapa di kota ini bisa ditemui tidak sedikit perkampungan orang Tioghoa dan juga situs-situs peninggalannya seperti tempat ibadah agama Konghucu. Disisi lain, di kota ini pula umat Muslim dengan tingkat keagamaan yang kuat tumbuh dan besar. Dengan pendekatan kualitatif, penelitian ini menemukan bahwa ada faktor yang turut membentuk enam model koeksistensi, toleransi, dan penghargaan terhadap perbedaan keyakinan diantara mereka. Pertama, integrasi sosial, kedua, asimilasi budaya, ketiga kooperasi bisnis, keempat selebrasi seremonial, kelima pelestarian budaya, dan keenam sinkritisme agama. Data yang dianalisis diperoleh melalui observasi dan interview dengan berbagai pihak yang merupakan objek penelitian ini, seperti kyai dan santri di empat pondok pesantren tertua di Lasem, tokoh dan masyarakat Tioghoa beragama Konghucu, dan juga dokumen-dokumen yang menerangkan historisitas Muslim dan Tionghoa di Lasem.